1972
DOI: 10.1021/jm00277a004
|View full text |Cite
|
Sign up to set email alerts
|

Metabolites of probenecid. Chemical, physical, and pharmacological studies

Abstract: Probenecid, its metabolites (including 14C labeled), and several analogs were synthesized. The uv spectral properties, p.Ka's, and partition coefficients were determined. The binding of probenecid and metabolites to human plasma, human albumin, and dog plasma was measured. Pmr parameters of probenecid, its metabolites, and 9 other analogs were obtained. There was no correlation between the nature of the alkyl side-chain substituents or the partition coefficient and the chemical shifts of the aromatic ring prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1972
1972
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…A major metabolic pathway of probenecid, which contains a carboxylic acid, is acyl glucuronidation in humans (Israili et al, 1972). Severe allergic or anaphylactoid reactions are known as adverse effects of probenecid (Hillecke, 1965).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A major metabolic pathway of probenecid, which contains a carboxylic acid, is acyl glucuronidation in humans (Israili et al, 1972). Severe allergic or anaphylactoid reactions are known as adverse effects of probenecid (Hillecke, 1965).…”
Section: Discussionmentioning
confidence: 99%
“…Reported side effects of probenecid include severe allergic, anaphylactoid reactions, and massive liver necrosis associated with the hypersensitivity reaction (Hillecke, 1965). Probenecid is extensively metabolized in humans via acyl glucuronidation and oxidation of alkyl side chains (Israili et al, 1972). Approximately 40% of the dose is eliminated as probenecid acyl glucuronide (PRAG) in urine within 48 hours, and excretion of the other metabolites, including 2-hydroxylprobenecid (7.2-12.5%), 3-hydroxyprobenecid (1.6-3.7%), carboxyprobenecid (6.3-9.2%), and N-depropylprobenecid (4.6-8.0%) as well as unchanged probenecid (,4%), was lower than that of PRAG (Perel et al, 1970) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Argon was the carrier; a hydrogen flame detector and temperature programming (up to 250 °C) was used. Reference standards of probenecid and the metabolites were synthesized (7,8) and converted to their respective methyl esters for calibration.…”
Section: Chemical Methodsmentioning
confidence: 99%
“…Plates were developed (benzene, EtOAc, HOAc, 7:3:1 v/v) dried and sprayed with H ,0 for visualization (Rf values: probenecid 0.70, N-depropyl 0.58, COOH 0.54, 2-OH 0.46, 3-OH 0.36, conjugates <0.1). The silica gel zones were scraped and counted in 18 ml liquid scintillation fluid (prepared by mixing 3 1 toluene with 21 g PPO, 1.08 g POPOP and 600 ml BBS-3) (8).…”
Section: On Disposition Of Probenecid In Patients Receiving Allopurinolmentioning
confidence: 99%
“…Previous studies have reported dose-dependent elimination of probenecid [Selen et al, 1982;Dayton et al, 1963;Benet, 1981, 1984;Emanuelsson and Paal zow, 1988;Emanuelsson et al, 1987], Inves tigations of different elimination pathways have been performed both in vivo and in vitro [Israili et al, 1972;Guarino et al, 1969;Perel et al, 1970Perel et al, , 1971Dayton and Perel, 1971;Dayton et al, 1973;Cunningham et al, 1977Cunningham et al, , 1981, and hepatic metabolism has been found to be the major pathway with oxidation of one of the alkyl side chains as the favoured step. The renal elimination of unchanged probenecid in man and dog seems to be responsible for only 5% of the administered dose [Perel et al, 1970;Beyer et al, 1951;Melethil and Conway, 1976], In a previous study the kinetics of pro benecid in the rat has been evaluated after intravenous bolus doses [Emanuelsson and Paalzow, 1988], and the results indicated both saturable protein binding and saturable elimination.…”
Section: Introductionmentioning
confidence: 99%